Pain in women with and without bipolar spectrum disorder - Stuart, Amanda L.; Berk, Michael; Pasco, Julie A.; Mohebbi, Mohammadreza; Quirk, Shae E.; Williams, Lana J. (Frontiers in Global Women's Health, 2025)
IntroductionBipolar disorder is associated with several physical conditions and possibly increased pain, although research outside hospital settings is limited. We compared perceived pain among population-based women with and without bipolar disorder.MethodThis study examined 113 women with bipolar disorder (59 euthymic, 54 symptomatic in past month) and 316 age-matched women without bipolar disorder drawn from studies located in the same region of south-eastern Australia. Mental disorders were confirmed by clinical interview (SCID-I/NP). Pain during the past week was determined by numeric rating scale (0–10, 10 = pain as severe as I can imagine) and deemed present if ≥5. Demographic, lifestyle, and health information was obtained via questionnaire. Odds ratios (OR) with 95% confidence intervals for the likelihood of pain were estimated using marginal binary logistic regression models, adjusting for potential confounders.ResultsWomen with bipolar disorder who were euthymic at the appointment were at increased odds of headache [adjOR 3.4, 95% CI (1.4, 7.9)], back pain [2.6 (1.3, 5.4)], overall pain(s) [5.7 (2.9, 11.4)], pain at ≥3 sites [2.3 (1.0, 5.2)] and were in pain ≥50% time spent awake [2.3 (1.1, 5.1)] compared to women without bipolar disorder. The pattern of association was similar but stronger for women symptomatic in the past month; headache [6.0 (2.6, 13.9)], back pain [4.2 (2.0, 8.5)], overall pain(s) [7.2 (3.4, 15.4)], pain at ≥3 sites [5.1 (2.3, 11.1)] and ≥50% time in pain [4.5 (2.2, 9.3)]. Daily activity interference from pain did not differ between groups (all p > 0.05).ConclusionWomen with bipolar disorder are more likely to report pain regardless of phase. Assessment and management of pain is necessary to reduce associated burden.